SpaceTime of the Imperial - Meyer, Holt 1961-; Rau, Susanne 1969-; Waldner, Katharina 1965- (Berlin Boston De Gruyter Oldenbourg, 2017)
In diesem Band geht es um Raumzeit-Konzepte imperialer Herrschaftspraktiken von der Antike bis zur Gegenwart und ihre Repräsentationen in verschiedensten Medien. International renommierte Wissenschaftler beleuchten das Thema aus historiographischer, kartographischer, religionswissenschaftlicher, literatur- bzw. medien-wissenschaftlicher sowie ethnographischer Perspektive.
Frontmatter -- -- Contents -- -- “… this smooth space of Empire … ” -- -- Reflecting on Narrative Othering through Imperial TimeSpaces -- -- Introduction. Reflecting on Narrative Othering through Imperial TimeSpaces -- -- Enchantments and Incitements: Modernity, Time/Space, Margins -- -- Imperiality, Deep Time, and Indigenous Landmark Epistemologies in North America -- -- In Other Times: Apocalypse, Temporality, Spatiality in Eastern India -- -- Gender in the Empire -- -- Introduction. Gender in the Empire -- -- “If I were King” – Photographic artifacts and the construction of imperial masculinities in the Philippine-American War (1899–1902) -- -- Beyond Blindness, Bias, and Marginalisation -- -- Europe, Spatiotemporal Orientation, and the Imperial -- -- Introduction. Europe, Spatiotemporal Orientation, and the Imperial -- -- Die neuzeitliche Narration „Europa“ und ihr imperialer Anspruch -- -- Alexander von Humboldt’s Interest in America: In the Service of Empire or of Humanity? -- -- Zum Pol -- -- God(s) in the Empire: Mapping Imperial Religion -- -- Introduction. Empire and Religion -- -- Early Christian Martyrology, Imperial Thirdspace and Mimicry -- -- Die Macht des Schicksals? -- -- Ästhetische Formationen der RaumZeit -- -- Cartographies of the Imperial Age -- -- Introduction. Spatiotemporalities of Cartographic Empire-Building -- -- The Spatial Anxieties of Everyday Colonial Rule and the History of Cartography: Connecting the Dots -- -- Mapping a Distant Empire: Bruno Hassenstein’s Atlas of Japan (1885/87) -- -- Void into Meaning: Geophysics and Imperial Cartography in the High Arctic -- -- Media Narratives on Königsberg/Kaliningrad: Spatiotemporalities of the Displaced -- -- Introduction. Temporal and Spatial Displacement: German and Russian Persons, Names and Cities in Königsberg/Kaliningrad -- -- Post-Imperial Narratives of Displacement in Germany around 1951 -- -- Displacement and its Nationalist Totalitarian Compensations in Puschdorf/Pushkino -- -- Der Traum von Klein-Moskau im Westen -- -- About the authors -- -- Index of persons -- -- Index of places and spaces
Mode of access: Internet via World Wide Web.
In English
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Space and time -- History -- Congresses; Imperialism -- Congresses; Space perception -- History -- Congresses; Time perception -- History -- Congresses; History -- Philosophy -- Congresses; Imperialismus; Raumzeitsystem; Wissenschaft; HISTORY / Modern / 17th Century; HISTORY / Social History; HISTORY / Modern / 19th Century; HISTORY / General; HISTORY / Modern / 18th Century